A Pragmatic Cluster-Randomized Trial of a Standing Order Entry Intervention for Colony-Stimulating Factor Use Among Patients at Intermediate Risk for Febrile Neutropenia. Issue 3 (13th October 2022) - Hershman, Dawn L.; Bansal, Aasthaa; Sullivan, Sean D.; Barlow, William E.; Arnold, Kathryn B.; Watabayashi, Kate; Bell-Brown, Ari; Le-Lindqwister, Nguyet A.; Dul, Carrie L.; Brown-Glaberman, Ursa A.; Behrens, Robert J.; Vogel, Victor; et al.
Abstract : PURPOSE: Primary prophylactic colony-stimulating factors (PP-CSFs) are prescribed to reduce febrile neutropenia (FN) but their benefit for intermediate FN risk regimens is uncertain. Within a pragmatic, randomized trial of a standing order entry (SOE) PP-CSF intervention, we conducted a substudy to evaluate the effectiveness of SOE for patients receiving intermediate-risk regimens. METHODS: TrACER was a cluster randomized trial where practices were randomized to usual care or a guideline-based SOE intervention. In the primary study, sites were randomized 3:1 to SOE of automated PP-CSF orders for high FN risk regimens and alerts against PP-CSF use for low-risk regimens versus usual care. A secondary 1:1 randomization assigned 24 intervention sites to either SOE to prescribe or an alert to not prescribe PP-CSF for intermediate-risk regimens. Clinicians were allowed to over-ride the SOE. Patients with breast, colorectal, or non–small-cell lung cancer were enrolled. Mixed-effect logistic regression models were used to test differences between randomized sites. RESULTS: Between January 2016 and April 2020, 846 eligible patients receiving intermediate-risk regimens were registered to either SOE to prescribe (12 sites: n = 542) or an alert to not prescribe PP-CSF (12 sites: n = 304). Rates of PP-CSF use were higher among sites randomized to SOE (37.1% v 9.9%, odds ratio, 5.91; 95% CI, 1.77 to 19.70; P = .0038). Rates of FN were low and identical between arms (3.7% v 3.7%). CONCLUSION: Although implementation of a SOE intervention for PP-CSF significantly increased PP-CSF use among patients receiving first-line intermediate-risk regimens, FN rates were low and did not differ between arms. Although this guideline-informed SOE influenced prescribing, the results suggest that neither SOE nor PP-CSF provides sufficient benefit to justify their use for all patients receiving first-line intermediate-risk regimens.